2002
DOI: 10.1103/physrevb.65.214509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn and Ni substitution on the local electronic structure of theYBa2Cu3O

Abstract: Embedded cluster calculations at the MP2 electron correlation level of pure and Zn-and Ni-doped YBa 2 Cu 3 O 7 (Y123) ceramics reveal great changes of the local charge distribution and crystal bonding in the vicinity of impurities. In the Zn-doped ceramics the obtained changes are stronger and more extended than in the Ni-doped ceramics. This can be one of explanations of the stronger depression of T c due to Zn. The calculated increase of positive charge for both impurities, comparing with substituted Cu, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 56 publications
3
24
0
1
Order By: Relevance
“…on the four next nearest oxygen atoms. This result is in agreement with that obtained previously by Kaplan et al 2 . For a comparison of the effects of Zn substitution with those of hole doping, we then simulated a hole doping of about 8 % in unsubstituted La 2 CuO 4 by removing one electron from the Cu 13 cluster and observed that in general impurity substitution seems to compensate the effects of hole doping on the charge distribution.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…on the four next nearest oxygen atoms. This result is in agreement with that obtained previously by Kaplan et al 2 . For a comparison of the effects of Zn substitution with those of hole doping, we then simulated a hole doping of about 8 % in unsubstituted La 2 CuO 4 by removing one electron from the Cu 13 cluster and observed that in general impurity substitution seems to compensate the effects of hole doping on the charge distribution.…”
Section: Discussionsupporting
confidence: 94%
“…These methods which are not based on periodic lattice structures, are particularly suited to calculate the changes in the charge and spin density distributions that are occurring upon the replacement of a regular atom by a new species. Cluster calculations for Zn and Ni substituted YBa 2 Cu 3 O 7 have previously been reported by Kaplan et al 2 using clusters with five copper atoms in the CuO 2 plane for the pure material. They employed Møller-Plesset perturbation theory to investigate on the differences in the atomic charges between unsubstituted and impurity substituted clusters.…”
Section: Introductionmentioning
confidence: 94%
“…The initial strong assumption allows us to use the tools of density functional theory (DFT) 17,18 to ensure that the full electronic structure of BSCCO and the local chemistry of the impurities are properly accounted for. Although we believe that this is a reasonable attempt to capture some of the qualitative systematics of the impurity problem, and some similar approaches have been tried 19 , it is not a priori obvious that such a calculation method can succeed. This is because density functional theory is known to fail for the high-T c parent compounds, which are anti-ferromagnetic Mott insulators.…”
Section: Introductionmentioning
confidence: 99%
“…The doping of Zn þ 2 at Cu þ 2 sites in CuO 2 planes in d-wave high temperature superconductors (HTSC's) was suggested to be the source of pair-breaking mechanism and electronic localization in the neighborhood of Zn-doped atoms [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. It was suggested that in YBa 2 Cu 3 O 7À d superconductor, localization of carriers at Cu þ 2 sites in the CuO 2 planes in the immediate vicinity of Zn þ 2 suppresses superconductivity [12].…”
Section: Introductionmentioning
confidence: 99%